Psoriasis and cardiovascular risk: Immune-mediated crosstalk between metabolic, vascular and autoimmune inflammation. (March 2015) - Kölliker Frers, R.A.; Bisoendial, R.J.; Montoya, S.F.; Kerzkerg, E.; Castilla, R.; Tak, P.P.; Milei, J.; Capani, F.
Abstract: Introduction and background: In the last few years, a substantial body of evidence indicates that cutaneous psoriasis and psoriatic arthritis patients are at higher risk of developing cardiovascular disease. However, underlying mechanism remains not completely understood. In this review we discuss the role of the immune system in the development of atherosclerosis, focusing on available data implicating the role of an enhanced immune-mediated proinflammatory status in psoriasis and psoriatic arthritis diseases. Methods: A systematic search was performed on Pubmed until November 2014, with preference to the sources published within the past 8 years, including epidemiological studies (prospective and retrospective); cross-sectional case–control studies and reviews. Articles were selected according critical associations using the following keywords: arthritis, immune-mediated inflammatory diseases, and psoriasis. These were combined with closely related keywords reflecting cardiovascular diseases: atherogenesis, endothelial dysfunction, intima media thickness, subclinical atherosclerosis, plaque, thrombosis, thrombus, fibrinolysis, coagulation, and reactive oxygen species. Both types of disease selected terms were separately combined with non-traditional (innate and adaptive pro and anti-inflammatory immune molecules and cells) and traditional (metabolic related conditions and molecules) cardiovascular risk factors. Results and conclusions: Psoriasis and psoriatic arthritis diseases illustrate that immune-mediated activated crossroads of inflammation beyond enhanced cardiovascular risk factors are the result of an interplay between different proatherogenic mediators derived from metabolic, vascular and autoimmune joint and skin inflamed target tissue. Consistent with this point of view, psoriasis and psoriatic arthritis diseases offer an invaluable opportunity to reinforce our knowledge about atherosclerotic cardiovascular disease.